Analyzing the Conceptual Framework and Policy Measures for Improving the Agricultural Trade: Analyzing India's Agricultural Trade and Food Security (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The agricultural sector has been crucial to India's progress toward its Aatmanirbhar Bharataim, as well as the generation of much-needed foreign cash via the sale of agricultural goods. Thisresearch attempts to examine the patterns and outcomes of agricultural commerce from fiscal year1990–1991 to fiscal year 2020–2021, with the last year coinciding with the COVID–19 epidemic. Using justavailable secondary sources. The first three months of 202122 saw an increase in agri-imports, vegetableoils leading the way, followed by raw and waste cotton, and then fresh fruits and vegetables. The datawas compiled and analysed using standard tabular formats, visual representations of the data, thecompound annual growth rate (CAGR), and the coefficient of variation. Thus, India has shown aremarkable development curve, going from a food-insecure nation to one that is both food-secure andfood-abundant. India is now a net exporter of agricultural output thanks to a series of revolutions inagricultural productivity spurred on by technologies, incentives, and institutions.